The effect of incorporating slurries on the transport of faecal coliforms in overland flow. - Quinton, John Norman; Tyrrel, Sean F.; Ramos, María C. (Blackwell Publishing Ltd., 2003)
Rainfall simulation experiments on a laboratory soil flume were conducted to test the hypothesis that the incorporation of slurry into the soil would reduce bacterial transport in overland flow. Presumptive faecal coliform (PFCs) concentrations were higher in the runoff from the surface applied treatment than from the incorporated treatments. The transport of PFCs and organic sediment were strongly correlated, with values of r ranging from 0.72 to 0.91.
Keywords: Slurry; faecal coliforms; pathogen transport; overland flow; slurry management; diffuse pollution